Utility of radial endobronchial ultrasonography combined with transbronchial lung cryobiopsy in patients with diffuse parenchymal lung diseases: a multicentre prospective study. Issue 1 (13th January 2021) - Inomata, Minoru; Kuse, Naoyuki; Awano, Nobuyasu; Tone, Mari; Yoshimura, Hanako; Jo, Tatsunori; Minami, Jonsu; Takada, Kohei; Muto, Yutaka; Fujimoto, Kazushi; Harada, Akinori; Bae, Yuan; et al.
Abstract : Background: Radial endobronchial ultrasonography (R-EBUS) has been used in conjunction with transbronchial lung cryobiopsy (TBLC) to diagnose diffuse parenchymal lung disease (DPLD) and to decrease the risk of bleeding complications. The diagnostic utility of different R-EBUS signs, however, remains unknown. Objectives: This study aimed to determine whether different R-EBUS signs could be used to more accurately diagnose DPLD and whether bronchial bleeding could be prevented with use of R-EBUS during TBLC. Method: Eighty-seven patients with DPLD were included in this multicentre prospective study, with 49 patients undergoing R-EBUS. R-EBUS signals were characterised as displaying either dense or blizzard signs. Pathological confidence of specimens obtained from TBLC was compared between patients with dense versus blizzard signs, and severity of bronchial bleeding was determined based on whether R-EBUS was performed or not. Results: All patients with dense signs on R-EBUS showed consolidation on high-resolution CT (HRCT) imaging. Pathological confidence of lung specimens was significantly higher in patients with dense signs versus those with blizzard signs (p<0.01) and versus those who did not undergo R-EBUS (p<0.05). Patients who underwent TBLC with R-EBUS were more likely to experience no or mild bronchial bleeding than patients who did not undergo R-EBUS (p<0.01), with shorter procedure times (p<0.01). Conclusions: The dense R-EBUS sign corresponded with consolidation on HRCT. High-quality lung specimens may be obtainable when the dense sign is observed on R-EBUS, and R-EBUS combined with TBLC may reduce risk of bronchial bleeding and shorten procedure times.